Significantly Delayed Development of Polyarthritis with Active Tenosynovitis after Possible Temporary Neutropenic Immune-Related Adverse Events Caused by Atezolizumab Treatment: A Novel Case Report - Yoshitaka Saito; Yoh Takekuma; Hajime Asahina; Ryo Hisada; Mitsuru Sugawara (Case Reports in Oncological Medicine)
Immune checkpoint inhibitors have drastically improved cancer treatment. However, they may induce immune-related adverse events (irAEs). Here, we report a case of significantly delayed rheumatic irAEs (Rh-irAEs) with prior possible temporary neutropenic irAEs in a patient with atezolizumab-treated non-small-cell lung cancer and its management. A man in his sixties received atezolizumab monotherapy as the sixth-line treatment. He experienced an infusion-related reaction (fever) during the first cycle. On day 22 of cycle 2, grade 4 neutropenia suddenly appeared, but it disappeared on the next day. Cycle 3 was initiated after seven days; the patient did not exhibit any symptoms for approximately 500 days. However, on day 534 (day 1 of cycle 21), the patient complained of pain in the shoulders, back, and wrists. On day 644, the shoulder and back pain worsened with obvious swelling of the fingers. We thus suspended treatment and consulted a rheumatologist. A diagnosis of polyarthritis with active tenosynovitis was made based on joint ultrasound and laboratory tests. Prednisolone 15 mg attenuated the symptoms, allowing suspension of analgesics; however, dose reduction from 15 mg/day was difficult because of symptom flares. Finally, iguratimod 25 mg twice daily was initiated on day 764; prednisolone was reduced to 10 mg without flares, and its dosage was slowly reduced to 5 mg/day. Although irAEs exhibit multisystem features, delayed development of polyarthritis with active tenosynovitis after possible temporary neutropenic irAEs is rare. Thus, irAEs need to be monitored for a long time in patients with suspected irAE development even if it appears transiently.